A case of ventricular fibrillation without left ventricular systolic dysfunction induced by trastuzumab emtansine for breast cancer. Issue 4 (April 2022) - Takeda, Morihiko; Takada, Tsuyoshi; Shiba, Nobuyuki
Abstract: Trastuzumab-induced cardiomyopathy is a known complication of its use in breast cancer treatment. However, cardiac complications of trastuzumab without left ventricular systolic dysfunction have been rarely reported. These include left bundle branch block, sinus node dysfunction, and ventricular tachycardia. We herein report a case of a 47-year-old female with human epidermal growth factor receptor 2-positive, stage IV breast cancer without a history of cardiovascular disease. During treatment with trastuzumab emtansine (T-DM1), she presented with out-of-hospital cardiac arrest and was resuscitated by automated cardioverter defibrillator (AED). Emergent cardiac catheterization revealed no organic obstruction and coronary vasospasm in her coronary arteries, and no left ventricular systolic dysfunction. Ventricular fibrillation (VF) was documented by an event memory of AED. T-DM1 was withdrawn and implantable cardioverter defibrillator was implanted. Thereafter, VF or life-threatening arrhythmia were not documented for 36 months until her death by breast cancer. We concluded that the etiology of her VF event was T-DM1-induced cardiotoxicity. We believe this is the first report of life-threatening VF event without cardiomyopathy induced by T-DM1. <Learning objective: Trastuzumab emtansine (T-DM1) therapy for breast cancer has been associated with an increased risk of left ventricular dysfunction. However, non-myopathic cardiac complications of T-DM1 are rare. To our knowledge, this is the first report that describes a ventricular fibrillation without left ventricular dysfunction after taking T-DM1. We strongly suggest that not only monitoring of left ventricular systolic function, but heart-rhythm monitoring should be performed in patients taking T-DM1.>